Association of ADHD symptoms in adolescence and mortality in Northern Finland Birth Cohort 1986. (1st February 2023) - Mustonen, Antti; Alakokkare, Anni-Emilia; Scott, James G.; Halt, Anu-Helmi; Vuori, Miika; Hurtig, Tuula; Rodriguez, Alina; Miettunen, Jouko; Niemelä, Solja
Abstract: Background: Diagnosis of attention deficit hyperactive disorder (ADHD) has been associated with increased risk of mortality in large register samples. However, there is less known about the association between symptoms of ADHD in adolescents and risk of mortality in general population samples. Methods: The Northern Finland Birth Cohort 1986 ( n = 9432 at recruitment in early pregnancy) linked to nationwide register data for deaths was utilized to study the association between parent-rated ADHD symptoms assessed using Strengths and Weaknesses of ADHD symptoms and Normal Behaviors (SWAN) questionnaire and mortality until age 33 years. Cox-regression analysis with hazard ratios (HRs) and 95% confidence intervals (CIs) was used to study the association between SWAN inattentive, hyperactive, and combined symptom scores and risk of death. Results: Sixty-three (0.9%) of the 6685 participants died during the follow-up. Higher SWAN inattentive (crude HR = 2.30, 95% CI 1.46–3.63), SWAN hyperactive (crude HR = 2.43, 95% CI 1.29–4.56), and SWAN combined (crude HR = 2.69, 95% CI 1.57–4.61) scores were associated with increased risk of death. After adjustments for sex, family structure, and lifetime parental psychiatric disorder, these associations persisted. Further adjustment for frequent alcohol intoxication, cannabis, and other substance use in adolescence attenuated these to below statistical significance. Conclusions: These results extend previous findings on the risk of mortality in adolescents who have symptoms of ADHD. Further research with larger samples are needed to determine whether the association between ADHD symptoms and mortality is independent of adolescent substance use.